Histopathological study of soft tissue sarcomas seen in a teaching hospital in Kano, Nigeria - Yusuf, Ibrahim; Mohammed, Aminu; Iliyasu, Yawale (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background and Objective: Malignant soft tissue tumours account for less than 1% of overall human burden of malignant tumours. Increasing incidences of these tumours have been noted worldwide. This study aims to determine the pattern of soft tissue sarcomas seen in a teaching hospital.Materials and Methods: The study comprised of all cases of soft tissue sarcoma diagnosed over a 10-year review from 1 January 1999-31 December 2008.Results: A total of 264 cases of soft tissue sarcomas were reviewed; 162 males and 102 females with a male to female ratio of 1.6:1. The age range was between 3 months and 89 years with a mean age of 39.0 years. Kaposi sarcoma was the predominant histological type with 56 cases (21.2%). This was followed by rhabdomyosarcoma with 54 (20.5%) cases, dermatofibrosarcoma with 52 (19.7%) cases and liposarcoma with 32 (12.0%) cases. The most common site of affectation was the lower limb with 73 (27.7%) cases, followed by the trunk with 66 (25.0%) cases, head and neck with 45 (17.0%) cases and upper limb with 35 (13.3%) cases. Two hundred and eight cases satisfied the criteria for grading, out of which 34.1% were classified in grade I, 32.2% in grade II and 33.7% in grade III.Conclusion: Soft tissue sarcomas accounted for 8.8% of malignant tumours seen over the review period and Kaposi sarcoma was the predominant histological subtype commonly affecting young adults in our centre.
Keywords: Grading; histopathology; sarcoma; soft tissue